2019
DOI: 10.1002/pola.29403
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous reverse iodine transfer polymerization of acrylic acid

Abstract: The utilization of sodium iodide, potassium persulfate, and a thermal radical initiator enables facile access to PAA via the direct reverse iodine transfer polymerization of acrylic acid. This polymerization proceeds rapidly in aqueous media using inexpensive and commercially available reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…However, only a few reports address the controlled polymerization of acidic monomers and particularly AA. Nitroxide mediated polymerization (NMP), , reversible addition–fragmentation chain-transfer (RAFT) polymerization, reverse iodine transfer polymerization (RITP), and other techniques provided moderately controllable PAA synthesis, yet required high temperatures, long reaction times, and/or expensive and not readily available catalytic or chain-transfer systems. Thus, the most common way to prepare well-defined PAA is via RDRP of tert -butyl acrylate followed by deprotection of the tert -butyl group. The development of a procedure to prepare well-defined homo- and copolymers of AA with commercially available materials under mild conditions remains highly desirable.…”
mentioning
confidence: 99%
“…However, only a few reports address the controlled polymerization of acidic monomers and particularly AA. Nitroxide mediated polymerization (NMP), , reversible addition–fragmentation chain-transfer (RAFT) polymerization, reverse iodine transfer polymerization (RITP), and other techniques provided moderately controllable PAA synthesis, yet required high temperatures, long reaction times, and/or expensive and not readily available catalytic or chain-transfer systems. Thus, the most common way to prepare well-defined PAA is via RDRP of tert -butyl acrylate followed by deprotection of the tert -butyl group. The development of a procedure to prepare well-defined homo- and copolymers of AA with commercially available materials under mild conditions remains highly desirable.…”
mentioning
confidence: 99%
“…However, other techniques, such as iodine transfer polymerization, are also discussed. Hawker (a native Australian researcher from Brisbane) and co‐workers have investigated the use of reversible iodine transfer polymerization for the preparation of polyacrylic acid . In this work, the authors have shown the direct polymerization of acrylic acid in water in the presence of sodium iodine; the in situ synthesis of alkyl iodide provides a facile and cheap route to the production of an important commodity polymer (poly(acrylic acid)).…”
mentioning
confidence: 99%